Teaching and learning in secondary and post-secondary education: Views of undergraduate art and design students in the United Arab Emirates - Souleles, Nicos (My University, 2013)
Despite the investment in secondary and Higher Education (HE) in the UAE, student outcomes do not match expectations. For a country that aspires to join the global knowledge economy, this is a significant concern. This paper focuses on the views of undergraduate art and design students in relation to their teaching and learning experiences during secondary school and the impact this has on their studies. More specifically, this paper argues that the lack of art and design subjects during secondary education has an overall detrimental effect on educational progress at the post-secondary level, which consequently hinders the development of competencies associated with the UAE’s aspiration to join the global knowledge economy. This is a small-scale qualitative study based on an online survey of thirty-eight undergraduate art and design students. The issues raised in this paper have implications for undergraduate art and design education in the UAE, and in particular how well prepared students are to undertake post-secondary education and how well equipped graduates are to join the global knowledge economy.
Keywords: Art; Design; Secondary Education; Higher Education; United Arab Emirates